2018
DOI: 10.2106/jbjs.17.01636
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and Remodeling of Structural Allografts in Acetabular Reconstruction

Abstract: Background:Total hip arthroplasty (THA) is frequently accompanied by acetabular bone loss, which constitutes a major challenge in revision procedures. Structural allografts can be implanted to restore a stable osseous foundation for the acetabular prosthesis. As previous studies were limited to clinical data or included very few cases, the extent to which the graft bone is incorporated over time has remained unclear.Methods:Thirteen acetabula were retrieved post mortem, and the incorporation properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 25 publications
2
24
1
7
Order By: Relevance
“…More specifically, a revascularization of the graft was followed by osteoclastic resorption and new bone formation on the graft. In structural allografts, successful incorporation and remodeling was also detected [ 9 ], however, this was most likely limited to the area of direct contact between the host bone and the allograft bone [ 30 ]. In general, the difference in the remodeling of chips and structural allografts may be explained by the different surgical techniques (i.e., impaction grafting vs. maintained structure).…”
Section: Allograft Incorporationmentioning
confidence: 99%
See 4 more Smart Citations
“…More specifically, a revascularization of the graft was followed by osteoclastic resorption and new bone formation on the graft. In structural allografts, successful incorporation and remodeling was also detected [ 9 ], however, this was most likely limited to the area of direct contact between the host bone and the allograft bone [ 30 ]. In general, the difference in the remodeling of chips and structural allografts may be explained by the different surgical techniques (i.e., impaction grafting vs. maintained structure).…”
Section: Allograft Incorporationmentioning
confidence: 99%
“…Regarding the time course of allograft incorporation, it was found that allograft chips had incorporated within the first 12 weeks after implantation [ 32 ]. In structural allografts, long-term follow up observations revealed no time-dependent increase in the incorporation between four years and 22 years after implantation [ 9 ].…”
Section: Allograft Incorporationmentioning
confidence: 99%
See 3 more Smart Citations